2015
DOI: 10.1152/japplphysiol.00875.2014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of blood flow occlusion on muscle oxygenation characteristics and the parameters of the power-duration relationship

Abstract: Broxterman RM, Ade CJ, Craig JC, Wilcox SL, Schlup SJ, Barstow TJ. Influence of blood flow occlusion on muscle oxygenation characteristics and the parameters of the power-duration relationship. J Appl Physiol 118: 880 -889, 2015. First published February 6, 2015 doi:10.1152/japplphysiol.00875.2014.-It was previously (Monod H, Scherrer J. Ergonomics 8: 329 -338, 1965 postulated that blood flow occlusion during exercise would reduce critical power (CP) to 0 Watts (W), while not altering the curvature constant (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
66
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 55 publications
9
66
1
Order By: Relevance
“…There was no further change in muscle deoxygenation with the onset of muscle contraction and the %Sat remained elevated above zero throughout each protocol. These results further support that muscle oxygenation decreases until the capillary-mitochondria PO 2 gradient attains equilibrium with the inherent resistance to diffusion (Ḋ O2 Ϫ1 ) (1), so that complete deoxygenation is not attained in the microvasculature (1,8,18,28,29) during blood flow occlusion.…”
Section: R688supporting
confidence: 57%
See 1 more Smart Citation
“…There was no further change in muscle deoxygenation with the onset of muscle contraction and the %Sat remained elevated above zero throughout each protocol. These results further support that muscle oxygenation decreases until the capillary-mitochondria PO 2 gradient attains equilibrium with the inherent resistance to diffusion (Ḋ O2 Ϫ1 ) (1), so that complete deoxygenation is not attained in the microvasculature (1,8,18,28,29) during blood flow occlusion.…”
Section: R688supporting
confidence: 57%
“…The depletion of intramuscular energy stores and accumulation of fatigueinducing metabolites consequent to the increased reliance on anaerobic energy production would be expected to diminish W= despite no mechanical work being performed (i.e., rest). Consistent with this, we have previously suggested that W= may be utilized in its entirety if the duration of resting blood flow occlusion is sufficient, despite no mechanical work being performed (1).…”
supporting
confidence: 67%
“…When the power-duration curve is measured, W′ has units of work, and thus only a small jump of logic is required to extrapolate this “amount of work” to a biological equivalent of stored energy. The early work of Monod and Scherrer (61) implied that this stored energy was of non-oxidative origin: a proposal recently supported by Broxterman et al (12,14) using occluded handgrip exercise. Intramuscular energy stores such as muscle glycogen and PCr are obvious targets, and indeed the cycle-ergometry W′ is increased following creatine supplementation (58,c.f., 101) and decreased following glycogen depletion (59).…”
Section: Unraveling the Power-duration Curvature Constant (W′) In Heamentioning
confidence: 94%
“…Using brachial occlusion in a hand-grip exercise model, Broxterman et al (12) reduced CP to less than zero, while W′ significantly increased. Putative explanations for this elevated W′ include: a) some of the oxidative ATP turnover normally quantified within CP appeared as W′, b) the muscle somehow accessed more substrate level phosphorylation, c) the efficiency of muscle contraction and/or ATP resynthesis increased.…”
Section: The Role Of Oxygen In Shaping the Power-duration Curvementioning
confidence: 99%
See 1 more Smart Citation